2006
DOI: 10.1159/000092219
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Antipsychotic Usage-Related Higher Serum Leptin Levels and Disabled Lipid Profiles in Euthymic Bipolar Patients

Abstract: Atypical antipsychotics (AA)-induced weight gain is associated with increased leptin levels. AA have been increasingly used in the treatment of bipolar disorders. This cross-sectional study aimed to evaluate the association between serum leptin and lipid profiles considering the drug treatments in euthymic bipolar outpatients. Leptin and lipid profiles were compared, and no differences were noted in leptin, cholesterol, and low-density lipoprotein levels among the patients and controls. Glucose, very-low-densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 70 publications
0
18
1
4
Order By: Relevance
“…These studies indicate conclusively that, when matched appropriately with nonpsychiatric subjects, patients with schizophrenia do not exhibit greater than expected serum leptin levels regardless of antipsychotic drug exposure (Baptista et al, 2001;Eder et al, 2001;Herran et al, 2001;Hagg et al, 2001;Zhang et al, 2003;Arranz et al, 2004;Sporn et al, 2005;Haupt et al, 2005;Gergerlioglu et al, 2006;Atmaca et al, 2007). The one controlled comparative study of medication-treated bipolar patients vs. matched controls also reported no significant difference in leptin levels between the psychiatric patients and their peers (Gergerlioglu et al, 2006).…”
Section: Diagnosis Effectsmentioning
confidence: 84%
See 3 more Smart Citations
“…These studies indicate conclusively that, when matched appropriately with nonpsychiatric subjects, patients with schizophrenia do not exhibit greater than expected serum leptin levels regardless of antipsychotic drug exposure (Baptista et al, 2001;Eder et al, 2001;Herran et al, 2001;Hagg et al, 2001;Zhang et al, 2003;Arranz et al, 2004;Sporn et al, 2005;Haupt et al, 2005;Gergerlioglu et al, 2006;Atmaca et al, 2007). The one controlled comparative study of medication-treated bipolar patients vs. matched controls also reported no significant difference in leptin levels between the psychiatric patients and their peers (Gergerlioglu et al, 2006).…”
Section: Diagnosis Effectsmentioning
confidence: 84%
“…These studies indicate conclusively that, when matched appropriately with nonpsychiatric subjects, patients with schizophrenia do not exhibit greater than expected serum leptin levels regardless of antipsychotic drug exposure (Baptista et al, 2001;Eder et al, 2001;Herran et al, 2001;Hagg et al, 2001;Zhang et al, 2003;Arranz et al, 2004;Sporn et al, 2005;Haupt et al, 2005;Gergerlioglu et al, 2006;Atmaca et al, 2007). The one controlled comparative study of medication-treated bipolar patients vs. matched controls also reported no significant difference in leptin levels between the psychiatric patients and their peers (Gergerlioglu et al, 2006). Interestingly, a 6-month prospective risperidone study in autistic children noted no increase in serum leptin levels despite a mean weight gain of 5.6 kg (Martin et al, 2004), Lastly, a single 12-week prospective trial compared the effects of olanzapine, risperidone and quetiapine for levodopa psychosis in 30 Parkinson's Disease (PD) patients, using one group of PD subjects (n=10) treated solely with antiparkinsonian medications and another unmedicated cohort (n=10) as controls (Rustembegovic et al, 2006).…”
Section: Diagnosis Effectsmentioning
confidence: 85%
See 2 more Smart Citations
“…Reports have been published on the metabolic effects of atypical antipsychotics and mood stabilizers. One study has shown that the use of atypical antipsychotics and mood stabilizers is associated with disordered lipids in euthymic bipolar patients [16], and the other study confirmed that only users of atypical antipsychotics (olanzapine, quetiapine, or risperidone) had higher metabolic syndrome rates than either users of atypical antipsychotics in combination with mood stabilizers (sodium valproate and/or lithium) or users of mood stabilizers alone [17]. In another retrospective study of bipolar patients receiving risperidone, olanzapine, or clozapine as an add-on to standard mood stabilizers, weight gain was significantly greater with olanzapine (4.0 kg) than with risperidone (2.4 kg) for 4 weeks, and the combination of divalproex and atypical antipsychotics caused more weight gain than did combination therapy with lithium [18].…”
mentioning
confidence: 99%